Benefits of Surgical Over Medical Treatment for Unilateral Primary Aldosteronism - Ahmed, Sumaiya; Hundemer, Gregory L. (Frontiers in Endocrinology, 2022)
Primary aldosteronism is the most common and modifiable form of secondary hypertension. Left untreated, primary aldosteronism leads high rates of cardiovascular, metabolic, and kidney disease. Therefore, early diagnosis and targeted therapy are crucial to improve long-term patient outcomes. In the case of unilateral primary aldosteronism, surgical adrenalectomy is the guideline-recommended treatment of choice as compared to alternative medical therapies such as mineralocorticoid receptor antagonist medications. Surgical adrenalectomy is not only highly successful in reversing the biochemical abnormalities inherent to primary aldosteronism, but also in mitigating the long-term risks associated with this disease. Indeed, as opposed to medical treatment alone, surgical adrenalectomy offers the potential for disease cure. Within this review article, we review the existing evidence highlighting the benefits of surgical over medical treatment for unilateral primary aldosteronism.